Some Fixed point results related to G-metric spaces (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In the present paper some fixed-point theorems for single mapping in complete G-metric spaces are established. Obtained results are the generalization of the previous results.